Situación actual de la integración del Diseño en las empresas manufactureras del Cantón Pelileo para la gestión creativa y de procesos productivos de la indumentaria en denim - Paredes, María Cristina (2018)
This study focuses on identifying strategies that allow the integration of design in denim clothing manufacturing companies in the Pelileo Canton, Tungurahua province. For this, factors that impede and facilitate the integration of this discipline in them are identified. Using the case study as a methodology, the research examines the current situation at the country level and the business sector in general of the Canton (macro environment) and the companies under study against design (micro-environment). Through a PESTEL analysis, the characteristics of the context are highlighted, in terms of political, economic, social, technological, ecological, legal and demographic factors and the SWOT tool allows to visualize the situation and perception of the companies under study.